Probabilistic Seismic Hazard Model of West Bengal, India. Issue 7 (3rd October 2017) - Maiti, Soumya K.; Nath, Sankar K.; Adhikari, Manik D.; Srivastava, Nishtha; Sengupta, Probal; Gupta, Arun K.
Abstract : We deliver a next-generation Probabilistic Seismic Hazard model of West Bengal based on improved seismogenic source characterization considering both the Layered Polygonal sources & Tectonic sources in the hypocentral depth range of 0–25 km & 25–70 km, seismic local-specific site condition, and adaption of appropriate region specific ground motion prediction equations in a logic tree framework. The surface consistent Probabilistic seismic hazard distribution in terms of Peak Ground Acceleration (PGA) & 5% damped Pseudo Spectral Acceleration (PSA) at different time periods for 10% probability of exceedance in 50 years have been generated and the design response spectra computed.